Adipose-Derived Stem Cells: Isolation, Characterization, and Differentiation Potential. Issue 4 (April 2013) - Huang, Shyh-Jer; Fu, Ru-Huei; Shyu, Woei-Cherng; Liu, Shih-Ping; Jong, Gwo-Ping; Chiu, Yung-Wei; Wu, Hsiao-Su; Tsou, Yung-An; Cheng, Chao-Wen; Lin, Shinn-Zong
In mammals, the two main types of adipose tissues, white and brown adipose tissues, exert different physiological functions. White adipose tissue (WAT) is for storing energy, while brown adipose tissue (BAT) is for energy consumption. Adipose-derived stem cells (ADSCs) are abundant in WAT and BAT, have multipotent characteristics, and are easily extracted. ADSCs can be differentiated into several cell lineages, including adipocytes, osteoblasts, chondrocytes (cartilage cells), myocytes, and neuronal cells. Therefore, ADSC could be considered as a strategy for future regenerative medicine and tissue engineering.